Peran Eva Peron dalam Memperjuangkan Hak Politik Perempuan di Argentina - Joshua C B Heumasse; Adhiningasih Prabhawati (Journal of Feminism and Gender Studies, 2022)
The years 1947-1952 were a breath of fresh air for Argentina. In the previous period, there were still no figures or policies that implemented and fought for the political rights of Argentine women. Maria Eva Duarte de Perón or commonly known as Eva Peron came to fight for women's political rights in Argentina. Eva Peron was the wife of Argentine President Juan Perón (1895-1974). Eva came from a simple family and then met her husband and became the First Lady and a very influential woman in Argentina. The purpose of this study was to determine and analyze the role of Eva Peron as the first lady in supporting and fighting for women's political rights in Argentina. The policies and organizations that she creates can realize women's real political rights.